CVB3-induced P62 cleavage promotes ferroptosis through the NRF2/GPX4 axis and facilitates viral replication - He, Feng; Liu, Zhuo; Feng, Miao; Cao, Dingding; Li, Sen; Liu, Xuelai; Jiang, Yiting; Yi, Xiaoyu; Liu, Zhewei; Yao, Hailan (Frontiers in Microbiology, 2025)
IntroductionCoxsackievirus B3 (CVB3) represents a major etiological agent of viral myocarditis, whose propagation within host organs results in substantial tissue injury. The molecular pathways through which CVB3 exerts its pathological effects, particularly its connection to ferroptosis-a regulated cell death modality characterized by iron-dependent lipid peroxidation-remain incompletely defined.MethodsWe employed a combination of in vitro and in vivo models of CVB3 infection. Molecular techniques including immunoblotting, gene manipulation, and viral assays were used to investigate the proteolytic processing of the selective autophagy receptor P62 and its functional consequences. The role of the KEAP1/NRF2/GPX4 axis was examined using a non-cleavable P62 mutant. Furthermore, the therapeutic potential of a selenium-rich diet was evaluated in infected mice.ResultsOur data showed that CVB3 replication induces the cleavage of P62 into distinct C- and N-terminal fragments. This event promotes the degradation of the transcription factor NRF2, leading to the downregulation of its target, GPX4, a key inhibitor of ferroptosis. Expression of a non-cleavable P62 mutant effectively stabilized the KEAP1/NRF2/GPX4 pathway and attenuated ferroptotic cell death in both cellular and mice models. Notably, GPX4 levels were not modulated by ubiquitination during infection. Supplementation with a selenium-rich diet, crucial for GPX4 synthesis, suppressed ferroptosis and improved survival rates in CVB3-infected mice.DiscussionThis study identifies a novel mechanism whereby CVB3 exploits the cleavage of P62 to inactivate the KEAP1/NRF2/GPX4 axis, thereby driving ferroptosis and disease progression. These findings highlight the therapeutic potential of restoring P62 function and supplementing selenium to alleviate CVB3-induced pathogenesis.